Measurement of mechanical response of cell membrane to high-frequency periodic stimuli - (:unkn) unknown (The Optical Society, 2020)
This study reports the holographic reconstruction method for capturing high frequency vibration patterns on live cell membranes. Periodic vibration patterns generated on cell membrane is recorded by modulation of a high-speed camera in real-time. © 2020 The Author(s)